Influence of Company Size and Debt to Equity Ratio (DER) on The Rent of Sukuk Ijarah - Jubaedah, Siti; Nurjanah, Nunung (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
This study aims to analyze the effect of company size and debt to equity ratio (DER) on fees from ijarah sukuk. The population in this study are companies that issue sukuk on the Indonesia stock exchange period 2013-2018. The method used is an associative method. The population in this study is the Indonesia stock exchange with a research year of 6 years 2013-2018. There were 6 samples of complains that issued ijarah sukuk on the indoneisa stock exchange that meet the criteria. The data collection technique uses secondary data in the form of published financial statements. Hypothesis testing is done using multiple linear analysis methods and testing using IBM SPSS version 22 software. The result showed that company size and debt to equity ratio (DER) doesn’t affect on fee of sukuk ijarah.